An effect of canopy bridges on monkey-vehicle collision hotspots: Spatial and spatiotemporal analyses - Cunneyworth, Pamela M K; Andrášik, Richard; Bíl, Michal (American journal of primatology, 2023)
Almost one-quarter of primate species are reported to be involved in vehicle collisions. To mitigate these collisions, canopy bridges are used though their effectiveness is not broadly substantiated. We studied bridge impact on 23 years of vehicle collisions (2000-2022: N = 765) with colobus (Colobus angolensis palliatus), Sykes' (Cercopithecus mitis albogularis), and vervet (Chlorocebus pygerythrus hilgerti) monkeys in Diani, Kenya. Along a 9 km road, collisions did not decrease over the study duration, although bridges increased from 8 to 30. Using the kernel density estimation plus (KDE+) method, collisions appeared highly concentrated at some locations. These concentrations, called hotspots, represent hazardous road segments, though the hotspots for all three species overlapped for only 3% of the road length. We then inspected the collision hotspots over time, using the spatiotemporal extension of the KDE+ method. We compared hotspot presence in the 3 years before and after bridge installation to determine if bridges mitigated these hotspots. Hotspots disappeared for ~60% of bridges postinstallation, suggesting that bridges effectively reduce some collisions. However, of the bridges installed in locations that were not hotspots, 13% had hotspots emerge. Surprisingly, regardless of preinstallation hotspot occurrence, almost one-fifth of bridges had postinstallation hotspots. To understand the extent to which bridges mitigate collisions, other factors need consideration, including species attributes and crossing behavior, and road features and vehicle volume. We used the novel analytical method because it best suited our data set, given the challenges of determining the bridge impact zone and the low collision frequency.
Keywords: Spatial Analysis; Animals; Chlorocebus aethiops; Accidents, Traffic; Colobus; Diani Kenya; Haplorhini; Primates; STKDE+; Haplorrhini; horizontal-ladder design; road overpass mitigation; Cercopithecus aethiops; zvířata; primáti; prostorová analýza; Spatio-Temporal Analysis; before-after study design; časoprostorová analýza; dopravní nehody